Eksplorasi Kualitas Pelayanan, Kepuasan dan Loyalitas Konsumen Bengkel XYZ Diesel - Praditya Kusuma; Saladin Ghalib (Program Magister Ilmu Administrasi Bisnis FISIP Universitas Lambung Mangkurat, 2025)
Abstract: The research method used is a qualitative approach, which allows researchers to gain an in-depth understanding of the quality of service provided by the XYZ DIESEL workshop according to loyal consumers. Data collection techniques are carried out through in-depth interviews. Key informants in this study are loyal consumers of the XYZ Diesel workshop, namely consumers from general workshop owners and mechanics, consumers from authorized workshops, and fleet user consumers. Tangible (Direct evidence), Reliability (reliability), Responsiveness (responsiveness), Empathy (empathy) and Assurance (Guarantee) show good results and these dimensions have an influence on Consumer Satisfaction at the XYZ Diesel workshop. The more attention is paid to the quality of service reflected, the more it will have an impact on increasing consumer satisfaction and creating customer loyalty XYZ Diesel, which can be seen from the aspect of willingness to recommend, repurchase, and convey positive word of mouth, but in this study the loyalty of respondents is more shown in the form of repurchase